2003
DOI: 10.1194/jlr.m200419-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Postprandial recruitment of neutrophils may contribute to endothelial dysfunction

Abstract: Atherosclerosis is a low-grade inflammatory disease involving leukocytes, lipids, and glucose leading to endothelial dysfunction. Since activation of neutrophils by triglycerides and glucose has been described in vitro, we hypothesized that the postprandial phase is an inflammatory state affecting leukocytes, possibly contributing to endothelial dysfunction. We measured postprandial blood leukocyte counts, cytokines, hydroperoxides (HPOs), and flow-mediated vasodilation (FMD) in eight healthy males (age 23 ؎ 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
170
4
7

Year Published

2004
2004
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 226 publications
(205 citation statements)
references
References 53 publications
20
170
4
7
Order By: Relevance
“…Consistent with previous studies [37][38][39], we found that plasmatic triacylglycerols and free fatty acids increased in plasma after a high-fat challenge in healthy men, and peaked 4 h after fat consumption (Fig. 1).…”
Section: Discussionsupporting
confidence: 81%
“…Consistent with previous studies [37][38][39], we found that plasmatic triacylglycerols and free fatty acids increased in plasma after a high-fat challenge in healthy men, and peaked 4 h after fat consumption (Fig. 1).…”
Section: Discussionsupporting
confidence: 81%
“…Il-8 concentration is increased after an oral glucose tolerance test in nondiabetic subjects [31]. WBCs increase after a meal [32], or glucose challenge with a significant increase of the plasma IL-8 level [33]. The results of this study that total WBC count was associated with postprandial glucose levels may reflect such postprandial inflammatory changes.…”
Section: Discussionsupporting
confidence: 49%
“…Both excessive eating and consuming a poor quality diet are associated with more systemic inflammatory stress. In the nonpregnant state, meals and especially fat rich meals cause transient inflammatory stress 63,64 which may be sustained if the intervals between meals are short.…”
Section: Oxidative and Inflammatory Stress And The Onset Of Preeclampsiamentioning
confidence: 99%